Evaluation of right and left heart mechanics in patients with chronic thromboembolic pulmonary hypertension before and after pulmonary thromboendarterectomy - YILDIZELİ, BEDRETTİN; MUTLU, BÜLENT; SÜNBÜL, MURAT (SPRINGER, 2015)
The aim of the present study was to evaluate of the right and left heart mechanics by two-dimensional (2D) speckle tracking echocardiography (STE) in chronic thromboembolic pulmonary hypertension (CTEPH) patients before and after pulmonary thromboendarterectomy (PTE). A total of 40 consecutive CTEPH patients (mean age 49.3 +/- A 13.5 years, 27 female) were included. 2D STE was performed in all patients before, and 3 months, after PTE. 12 months of prognostic data were also recorded via the use of telephone calls. Postoperative 6-minute walk test (6MWT) distances were significantly longer than preoperative values (410.5 +/- A 61.5 vs. 216.6 +/- A 131.4 m, p < 0.001). Postoperative left ventricular (LV) and right ventricular (RV) systolic functions (LV EF, TAPSE, RVS) were similar compared to preoperative values. While postoperative RV, right atrial (RA) and systolic pulmonary artery pressure measurements were significantly lower, LV and left atrial (LA) measurements were higher than preoperative values. Postoperative LV and RV global longitudinal strain (GLS) measurements were significantly higher than preoperative values. Postoperative LV global radial and circumferential strain measurements were similar to preoperative values. While postoperative RA reservoir and conduit functions were significantly higher, postoperative LA reservoir and conduit functions were similar to preoperative values. Correlation analysis revealed that baseline 6MWT distances were correlated with LV GLS, RV GLS, and RA reservoir and conduit functions in the preoperative and postoperative periods. 2D STE indices may help the clinician in assessing the effect of PTE on cardiac functions and may also be used for follow-up data in CTEPH patients.
Keywords: Chronic thromboembolic pulmonary hypertension; Ventricular functions; Atrial functions; Speckle tracking echocardiography; Pulmonary thromboendarterectomy; RIGHT-VENTRICULAR FUNCTION; SPECKLE-TRACKING STRAIN; ECHOCARDIOGRAPHIC-ASSESSMENT; DEFORMATION PARAMETERS; ARTERIAL-HYPERTENSION; EXERCISE CAPACITY; ATRIAL MECHANICS; ENDARTERECTOMY; UTILITY; RISK